Evaluation of the Time Spent by Anesthetist on Clinical Tasks in the Operating Room - Compère, Vincent; Besnier, Emmanuel; Clavier, Thomas; Byhet, Nicolas; Lefranc, Florent; Jegou, Frederic; Sturzenegger, Nicolas; Hardy, Jean Baptiste; Dureuil, Bertrand; Elie, Thomas (Frontiers in Medicine, 2022)
Background: Changes in the health system in Western countries have increased the scope of the daily tasks assigned to physicians’, anaesthetists included. As already shown in other specialties, increased non-clinical burden reduces the clinical time spent with patients. Methods: This was a multicenter, prospective, observational study conducted in 6 public and private hospitals in France. The primary endpoint was the evaluation by an external observer of the time spent per day (in minutes) by anaesthetists on clinical tasks in the operating room. Secondary endpoints were the time spent per day (in minutes) on non-clinical organizational tasks and the number of task interruptions per hour of work. Results: Between October 2017 and April 2018, 54 anaesthetists from 6 hospitals (1 public university hospital, 2 public general hospitals and 3 private hospitals) were included. They were followed for 96 days corresponding to 550 hours of work. The proportion of overall clinical time was 62% (58% 95%CI [53;63] for direct care. The proportion of organizational time was higher in public hospitals (11% in the university hospital (p0.001) and 4% in general hospitals (p0.01)) compared to private hospitals (1%). The number of task interruptions (1.5/h±1.4 in all hospitals) was 4 times higher in the university hospital (2.2/h±1.6) compared to private hospitals (0.5/h±0.3) (p0.05). Conclusions: Most time in the operating room was spent on clinical care with a significant contrast between public and private hospitals for organizational time.